Minimally invasive microsurgery for anterior communicating artery aneurism: lateral supra-orbitary approach plus intra-operatory fluorescein angiography - Salazar Campos, Cristian (2022)
Anterior communicating artery aneurisms (ACAA) are complex and require endovascular or microsurgery approaches. The use of minimally invasive microsurgery techniques is evolving. We present the case of a 34-year- old patient with a broad neck, non-broken, ACAA with a Glasgow coma scale of 15 points. A lateral supra-orbitary approach with total clipping of the ACAA using intra-operatory fluorescein angiography was performed. The objective was accomplished successfully and safe, optimizing both intra-operative and hospitalization times, thus, maximizing patient comfort, esthetic and prompt return to normal duties.